2008
DOI: 10.1210/en.2008-1001
|View full text |Cite
|
Sign up to set email alerts
|

Unique Roles of p160 Coactivators for Regulation of Breast Cancer Cell Proliferation and Estrogen Receptor-α Transcriptional Activity

Abstract: Each of the three members of the p160 steroid receptor coactivator (SRC) family of coactivators (SRC-1, SRC-2 and SRC-3) stimulates estrogen receptor (ER)-alpha function in trans-activation assays. Consequently, we sought to elucidate their contributions to the ER-regulated processes of cell proliferation, apoptosis, and the expression of ERalpha target genes in MCF-7 breast cancer cells. The small interfering RNA depletion of SRC-2 or SRC-3 but not SRC-1 inhibited growth of MCF-7 cells, and this was reflected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 43 publications
3
46
1
Order By: Relevance
“…Since estrogen and ER␣ signaling are important regulators in breast cancer, this raises the possibility that SMRT promotes breast tumorigenesis, at least in part through amplifying ER␣ target gene expression. Furthermore, overexpression of SMRT stimulated the intrinsic transcriptional activity of the oncogene steroid receptor coactivator 3 (SRC-3), itself an ER␣ coactivator and positive regulator of breast cancer cell proliferation, and together these coregulators cooperatively promoted estrogen-dependent expression of some but not all ER␣ target genes, including the cyclin D1 and progesterone receptor genes (29)(30)(31). Collectively, these candidate gene studies demonstrated that SMRT can coactivate ER␣ transcriptional activity in a gene-selective manner and indicated that SMRT has both coactivator and corepressor activities in breast cancer cells.…”
mentioning
confidence: 99%
“…Since estrogen and ER␣ signaling are important regulators in breast cancer, this raises the possibility that SMRT promotes breast tumorigenesis, at least in part through amplifying ER␣ target gene expression. Furthermore, overexpression of SMRT stimulated the intrinsic transcriptional activity of the oncogene steroid receptor coactivator 3 (SRC-3), itself an ER␣ coactivator and positive regulator of breast cancer cell proliferation, and together these coregulators cooperatively promoted estrogen-dependent expression of some but not all ER␣ target genes, including the cyclin D1 and progesterone receptor genes (29)(30)(31). Collectively, these candidate gene studies demonstrated that SMRT can coactivate ER␣ transcriptional activity in a gene-selective manner and indicated that SMRT has both coactivator and corepressor activities in breast cancer cells.…”
mentioning
confidence: 99%
“…As a coactivator for ER, AIB1 is thought to influence the growth of hormone-dependent breast cancer through mediating the effects of estrogen on ERα-dependent gene expression (2,41), and this serves as a mechanism by which AIB1 modulates the growth of hormone-dependent breast cancer. This mechanistic model is supported by a study showing that depletion of AIB1 may inhibit estrogen-stimulated cell proliferation and survival in ER-positive MCF-7 human breast cancer cells, leading to a decrease in growth of MCF-7 xenografts in mice (49,50). However, not all ERα-positive breast cancers are associated with higher levels of AIB1 mRNA, as ERα-negative breast cancer has also been found to be associated with high levels of AIB1 mRNA (14).…”
Section: Implication Of Aib1 In Breast Cancermentioning
confidence: 86%
“…Increased levels of SRC-2/TIF-2 mRNA have been observed in intraductal and invasive carcinoma compared to normal breast tissue (Kurebayashi et al, 2000;Haugan Moi et al, 2010). Knockdown of SRC-2/TIF-2 has been shown to inhibit growth of MCF-7 breast cancer cells due to decreased cell proliferation, increased apoptosis and reduced ER mediated transcriptional activity (Cavarretta et al, 2002;Karmakar et al, 2009). However, overall SRC-2/TIF-2 is the least studied of the coactivators in breast cancer.…”
Section: Src-2/tif-2mentioning
confidence: 99%
“…The oncogenic potential of SRC-3/AIB1 has been ascribed to mechanisms such as enhanced interaction between ER and the cyclin D1 promoter, hence leading to increased levels of cyclin D1 and stimulation of cell cycle progression (PlanasSilva et al, 2001). Conversely, cyclin D1 expression has been shown to be reduced in SRC-3/AIB1 knock-out cells (Karmakar et al, 2009), and mice with reduced SRC-3/AIB1 expression have a decrease in epithelial proliferation associated with a reduction in cyclin expression (Fereshteh et al, 2008). Overexpression of SRC-3/AIB1 also stimulates the Akt signaling pathway which promotes cell growth (Torres-Arzayus et al, 2004;Zhou et al, 2003).…”
Section: Src-3/aib1mentioning
confidence: 99%